O impacto da estimulação da consciência fonológica nas habilidades de leitura e escrita em indivíduos de desenvolvimento atípico – uma revisão crítica da literatura - Marques, Débora Mattos (Universidade do Vale do Rio dos Sinos, 2018)
It is almost consensual in the literature that phonological awareness is linked to reading and writing skills, and this has promoted research on individuals with different developmental trajectories who do not develop (or do it later) the ability to read and write fluently. The main objective of this dissertation is to do a critical review of papers that focus on the reinforcement of phonological awareness in individuals from four atypical populations: Williams Syndrome, Autism, Down Syndrome and Dyslexia, with potential impact on reading and writing skills. We searched papers on four databases, using keywords in Portuguese, English, and Spanish. The result is an amount of of 34 papers, analized in this study. The papers we found have shown that interventions focused on phonological awareness are favorable to the development of reading and writing skills in these populations, which raised some considerations about methodologies, training duration, number of informants, among other aspects.
Keywords: Consciência fonológica; Desenvolvimento atípico; Intervenção; Phonological awareness; Atypical development; Intervention.; ACCNPQ::Lingüística, Letras e Artes::Lingüística